Durvalumab, with or without tremelimumab, plus platinum-etoposide versus platinum-etoposide alone in first-line treatment of extensive-stage small-cell lung cancer (CASPIAN): updated results from a randomised, controlled, open-label, phase 3 trial - Goldman, Jonathan W; Dvorkin, Mikhail; Chen, Yuanbin; Reinmuth, Niels; Hotta, Katsuyuki; Trukhin, Dmytro; Statsenko, Galina; Hochmair, Maximilian J; Özgüroğlu, Mustafa; Ji, Jun Ho; Garassino, Marina Chiara; Voitko, Oleksandr; et al. (The Lancet. Oncology, 2021)
BACKGROUND: First-line durvalumab plus etoposide with either cisplatin or carboplatin (platinum-etoposide) showed a significant improvement in overall survival versus platinum-etoposide alone in patients with extensive-stage small-cell lung cancer (ES-SCLC) in the CASPIAN study. Here we report updated results, including the primary analysis for overall survival with durvalumab plus tremelimumab plus platinum-etoposide versus platinum-etoposide alone. METHODS: CASPIAN is an ongoing, open-label, sponsor-blind, randomised, controlled phase 3 trial at 209 cancer treatment centres in 23 countries worldwide. Eligible patients were aged 18 years or older (20 years in Japan) and had treatment-naive, histologically or cytologically documented ES-SCLC, with a WHO performance status of 0 or 1. Patients were randomly assigned (1:1:1) in blocks of six, stratified by planned platinum, using an interactive voice-response or web-response system to receive intravenous durvalumab plus tremelimumab plus platinum-etoposide, durvalumab plus platinum-etoposide, or platinum-etoposide alone. In all groups, patients received etoposide 80-100 mg/m2 on days 1-3 of each cycle with investigator's choice of either carboplatin area under the curve 5-6 mg/mL/min or cisplatin 75-80 mg/m2 on day 1 of each cycle. Patients in the platinum-etoposide group received up to six cycles of platinum-etoposide every 3 weeks and optional prophylactic cranial irradiation (investigator's discretion). Patients in the immunotherapy groups received four cycles of platinum-etoposide plus durvalumab 1500 mg with or without tremelimumab 75 mg every 3 weeks followed by maintenance durvalumab 1500 mg every 4 weeks. The two primary endpoints were overall survival for durvalumab plus platinum-etoposide versus platinum-etoposide and for durvalumab plus tremelimumab plus platinum-etoposide versus platinum-etoposide in the intention-to-treat population. Safety was assessed in all patients who received at least one dose of study treatment. This study is registered at ClinicalTrials.gov, NCT03043872. FINDINGS: Between March 27, 2017, and May 29, 2018, 972 patients were screened and 805 were randomly assigned (268 to durvalumab plus tremelimumab plus platinum-etoposide, 268 to durvalumab plus platinum-etoposide, and 269 to platinum-etoposide). As of Jan 27, 2020, the median follow-up was 25·1 months (IQR 22·3-27·9). Durvalumab plus tremelimumab plus platinum-etoposide was not associated with a significant improvement in overall survival versus platinum-etoposide (hazard ratio [HR] 0·82 [95% CI 0·68-1·00]; p=0·045); median overall survival was 10·4 months (95% CI 9·6-12·0) versus 10·5 months (9·3-11·2). Durvalumab plus platinum-etoposide showed sustained improvement in overall survival versus platinum-etoposide (HR 0·75 [95% CI 0·62-0·91]; nominal p=0·0032); median overall survival was 12·9 months (95% CI 11·3-14·7) versus 10·5 months (9·3-11·2). The most common any-cause grade 3 or worse adverse events were neutropenia (85 [32%] of 266 patients in the durvalumab plus tremelimumab plus platinum-etoposide group, 64 [24%] of 265 patients in the durvalumab plus platinum-etoposide group, and 88 [33%] of 266 patients in the platinum-etoposide group) and anaemia (34 [13%], 24 [9%], and 48 [18%]). Any-cause serious adverse events were reported in 121 (45%) patients in the durvalumab plus tremelimumab plus platinum-etoposide group, 85 (32%) in the durvalumab plus platinum-etoposide group, and 97 (36%) in the platinum-etoposide group. Treatment-related deaths occurred in 12 (5%) patients in the durvalumab plus tremelimumab plus platinum-etoposide group (death, febrile neutropenia, and pulmonary embolism [n=2 each]; enterocolitis, general physical health deterioration and multiple organ dysfunction syndrome, pneumonia, pneumonitis and hepatitis, respiratory failure, and sudden death [n=1 each]), six (2%) patients in the durvalumab plus platinum-etoposide group (cardiac arrest, dehydration, hepatotoxicity, interstitial lung disease, pancytopenia, and sepsis [n=1 each]), and two (1%) in the platinum-etoposide group (pancytopenia and thrombocytopenia [n=1 each]). INTERPRETATION: First-line durvalumab plus platinum-etoposide showed sustained overall survival improvement versus platinum-etoposide but the addition of tremelimumab to durvalumab plus platinum-etoposide did not significantly improve outcomes versus platinum-etoposide. These results support the use of durvalumab plus platinum-etoposide as a new standard of care for the first-line treatment of ES-SCLC. FUNDING: AstraZeneca.
Keywords: Small Cell Lung Carcinoma; Male; monoklonální protilátky; nádory plic; doba přežití bez progrese choroby; progrese nemoci; Antineoplastic Combined Chemotherapy Protocols; Lung Neoplasms; Neoplasm Staging; Carboplatin; Aged; etoposid; senioři; mužské pohlaví; Disease Progression; malobuněčný karcinom plic; karboplatina; humanizované monoklonální protilátky; Antibodies, Monoclonal, Humanized; Time Factors; lidé; ženské pohlaví; Humans; protokoly protinádorové kombinované chemoterapie; časové faktory; cisplatina; Antibodies, Monoclonal; Female; Progression-Free Survival; Cisplatin; lidé středního věku; staging nádorů; Etoposide; Middle Aged